A PILOT STUDY ON HOW DO ELITE SURFSKI PADLLERS MANAGE THEIR EFFORT AND HYDRATION PATTERN IN THE HEAT - O Hue; P Le Jeannic; K Chamari (Termedia Publishing House, 2014)
To investigate thermal response, hydration behaviour and performance over flatwater kayaking races in tropical conditions (36.8°C and 68 % rh). Five internationally-ranked subjects participated in the 2012 Surfski Ocean Racing World Cup in Guadeloupe to the "Ze Caribbean Race 2012" [i.e., a 35-km downwind race]. Core temperature (T°C) and heart rate (HR) were measured using portable telemetry units whereas water intake was deduced from backpacks absorption. The kayakers were asked to rate both their comfort sensation and thermal sensation on a scale before and after the race. The performance was related to an increase in T°C, high HR and low water intake (WI); and (2) high values of final T°C were related to high pre T°C and greater increases in T°C being obtained with low pre T°C and (3) WI being related to high pre T°C. The present study demonstrated that the fastest kayakers were those able to paddle at the highest intensities, increasing their T°C and drinking little water without any interference from thermal sensations. Water intake was positively related to pre-race T°C, which reinforces the importance of beginning surfski races with a low T°C. This study demonstrated that well-trained kayakers drinking ad libitum were able to anticipate their intensity/heat storage ratio to prevent heat illness and severe dehydration and maintain high performance.